2018
DOI: 10.1021/acs.molpharmaceut.8b00785
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Fraction Unbound in Human Plasma from Chemical Structure: Improved Accuracy in the Low Value Ranges

Abstract: Predicting the fraction unbound in plasma provides a good understanding of the pharmacokinetic properties of a drug to assist candidate selection in the early stages of drug discovery. It is also an effective tool to mitigate the risk of late-stage attrition and to optimize further screening. In this study, we built in silico prediction models of fraction unbound in human plasma with freely available software, aiming specifically to improve the accuracy in the low value ranges. We employed several machine lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 26 publications
1
106
0
Order By: Relevance
“…S4, a correlation could be seen between observed and predicted f u,p values ( r = 0.84), with 72.8% and 84.0% of the predicted f u,p values falling within 2-fold and 3-fold error, respectively. This indicated that the f u,p predicted by f u,p predictor 22 correlated well with the observed f u,p .…”
Section: Resultssupporting
confidence: 55%
See 3 more Smart Citations
“…S4, a correlation could be seen between observed and predicted f u,p values ( r = 0.84), with 72.8% and 84.0% of the predicted f u,p values falling within 2-fold and 3-fold error, respectively. This indicated that the f u,p predicted by f u,p predictor 22 correlated well with the observed f u,p .…”
Section: Resultssupporting
confidence: 55%
“…The compounds that displayed CR < 0.67, 0.67 ≤ CR < 1.5, or 1.5 ≤ CR were classified into reabsorption (R) type (net reabsorbed compounds), intermediate (IM) type (apparently not reabsorbed or secreted compounds), and secretion (S) type (net secreted compounds), respectively 5 . Predicted f u,p was calculated using our previously developed f u,p predictor 22 . Ionization profiles in the data set were extracted from the ChEMBL database.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This value was derived in silico using the fu,p Predictor software. [22] For rats, the f ub, blood was considered the same as for humans. Since the PBK models predict the AFB1 concentration in blood, for evaluation of the model performance, the plasma concentrations of AFB1 from in vivo kinetic studies were converted to blood concentrations to enable comparison to the model predictions, assuming that blood concentrations are 0.6 and 0.55 times the plasma concentrations in rats and humans, respectively.…”
Section: Fraction Unbound (F Ub ) In Plasma and Plasma To Blood Convementioning
confidence: 99%